Estimation of epistasis and genetic components of variance for different traits in cucumber (Cucumis sativus) - KUMARI, REENA; KUMAR, RAMESH; GUPTA, MEENU (The Indian Journal of Agricultural Sciences, 2021)
To estimate epistasis and components of genetic variance a study was carried out during 2016 and 2017 at Experimental Research Farm of Department of Vegetable Science, Dr YSP UH & F Nauni, Solan, (HP) and data were recorded for different qualitative and quantitative traits using triple test cross (TTC) analysis of an inter-varietal cross LC-1-1 × K-75 of cucumber (Cucumis sativus L.). Three testers of cucumber named LC-1-1, K-75 and their F1 (LC-1-1 × K-75) were crossed to 15 inbred lines for detecting the additive, dominance and epistatic components of genetic variance. Good quantum of genetic variability has been generated through triple test cross progenies with respect to different traits studied as revealed by the significant analysis of variance. TTC analysis revealed that overall epistasis and j+l type component were found to be significant for majority of the traits except fruit breadth and total soluble solids. Further, experimental results showed that (i) type of epistasis were also significant for majority of the traits under study. The components of genetic variance were estimated using analysis of variance for sums and differences revealed the importance of both additive (D) as well as dominance (H) components of genetic variance in controlling various traits and showed partial dominance except over dominance for fruit breadth and severity of downy mildew. Therefore, kind of genetic variance revealed from triple test cross can be exploited by intermating selected individuals in early segregating generations with delayed selection in later generations, or recurrent selection followed by pedigree method to exploit both additive and non-additive components along with epistasis in cucumber.